Issues Encountered during the Translation Process - El-Mokhtar, Ahmed Mohamed Lemine (Journal of Humanities & Social Sciences, 2023)
There are general translation problems that make translation a difficult activity. Some of these problems are related to source text, some related to target language and some to translation adopted methods and processes. This article enlists the most common issues and challenges translators encounter during the process of translation. It is divided into three sections. The first section is about the linguistic and cultural problems in translation. The second section illustrates certain constraints faced while translating idioms, metaphors and collocations. The third section highlights the duality of fidelity and freedom and the translator’s position in the process of translation.
Keywords: Translation Issues; linguistic and cultural problems in translation; Translating Idioms; Fidelity and Freedom in Translation